Collaborative Learning Melalui Diskusi Kelompok untuk Meningkatkan Prestasi Akademik dalam Kelas X MPLB SMKS Labor Binaan FKIP UNRI Pekanbaru Mata Pelajaran IPAS - Adza Noor Laila, Adinda Nurul Izzah Salma, Andi Cristin, Angel Sri Meilinda; Dina Alviola, Refa Seprianti, RM. Riadi; Yuli Wastuti (STKIP Subang, 2025)
This study aims to determine the effectiveness of the implementation of collaborative learning through group discussions in improving the academic achievement of class X students of Office Management and Business Services (MPLB) in the subject of Social Sciences at SMKS Labor Pekanbaru, University of Riau. This study uses the Classroom Action Research (CAR) method which is carried out in two cycles, each consisting of the planning, implementation, observation, and reflection stages. The results of the study showed an increase in the average value of students from 79.73 in cycle I to 85.06 in cycle II. Statistical tests with paired sample t-test showed a significant increase with a significance value of 0.000 (p <0.05), and an average increase in value of 4.97 points. As many as 81.8% of students experienced an increase in learning outcomes, and correlation analysis showed a significant positive relationship between values before and after treatment with a significance value of 0.018. In addition to having an impact on academic improvement, collaborative learning also strengthens students' social skills such as cooperation, communication, and responsibility. Thus, collaborative learning through group discussions has proven to be effective and worthy of being applied sustainably in the learning process.